Seagrass macroinvertebrate bycatches support mosquito net trawl fishery in Madagascar - Herinirina Patricia A.; Bigot Lionel; Frouin Patrick; Volandrae Huguette T.E; Randriatsara Roddy M.; Behivoke Faustinato; Ranivoarivelo Lantoasinoro; Léopold Marc (Aquatic Living Resources)
The use of mosquito nets, primarily for targeting small and/or juvenile fish, has rapidly increased in Western Indian Ocean shallow seagrass beds and coral reefs over the last 20 years. However, to date, invertebrate by-catch by locally-made fishing gear has not been reported. We studied the mosquito net trawl fishery in seagrass areas in the Bay of Toliara, Southwest Madagascar through the GPS tracking of fishers from August 2018 to February 2019. Catches were monitored through monthly landing surveys to characterize spatial temporal patterns in the abundance and diversity of macroinvertebrates in the seagrass beds. Fishing was carried out at low tide, mostly at night, by fishers pulling a hand-made trawl net of varying dimensions. Overall, 43 macroinvertebrate taxa were identified out of 217,080 individuals collected from 109 catch samples. Catches were generally composed of crustaceans (mainly Portunidae, Processidae, Penaeidae, and Alpheidae). The crab Thalamita mitsiensis largely dominated the abundance and biomass of the macroinvertebrate assemblage (from 6% to 100% and from 5 to 100% of the overall density and biomass, respectively). Macroinvertebrates composed 1.5% to 100% of the total catch per trip (i.e., 4–55 kg trip−1). They were sold for human consumption or animal feed, which provided additional income to fishers (USD 1–24 trip−1 and 1–72% of catch income per trip). This study revealed that macroinvertebrate resources provide valuable by-catch to small-scale fishers in Southwest Madagascar. This bycatch generates income that further encourages the use of mosquito net trawls and exacerbates their negative effects on coastal seagrass ecosystems and fisheries.